Managerial dilemmas in developing countries business, marketing, finance and tourism - Mohamed Aslam Gulam Hassan; Cooper, Malcolm J. M.; Gnanapala, Athula; Gamage, Thilini (Cambridge Scholars Publishing, 2019)
Since organizations and industries are the catalysts for sustainable development, managing organizations and industries along with resource protection dilemmas is critical for developing countries. This volume brings together contributions from experts and new researchers on managerial dilemmas in developing countries, and is divided into five parts: namely, organizational development; human resource management; consumer behaviour; finance; and tourism and hospitality.The chapters in the first section provide empirical insights into e-learning systems, information systems for decision-making p.